2021
DOI: 10.21608/jppp.2021.52745.1007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Metabolites of Myrothecium verrucaria as Biological Nematicide against Root-knot Nematode, Meloidogyne incognita in Vitro and in Vivo on Sugar Beet Plants

Abstract: Nematicidal activity of heat-sterilizing filtrate culture of Myrothecium verrucaria was evaluated against Meloidogyne incognita in Vitro and the metabolites formulated as granules of M. verrucaria were prepared and tested on sugar beet plants infested with M. incognita comparison with DiTera™ and Rugby 10%G, under greenhouse conditions. Laboratory results showed that sterilized culture filtrate of the fungus M. verrucaria either by syringe or by autoclaving significantly reduced the percentages of egg hatching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…In other studies, it was found to inhibit eggs from hatching by a nematostatic effect on the J2 of M. javanica, preventing early root invasion [45,46]. Application of this nematicide also reduced galling in beet plants infested by M. incognita by up to 86% [47]. However, in the 120 days after transplanting evaluation of our study, it performed poorly and matched the untreated control population.…”
Section: Discussioncontrasting
confidence: 49%
“…In other studies, it was found to inhibit eggs from hatching by a nematostatic effect on the J2 of M. javanica, preventing early root invasion [45,46]. Application of this nematicide also reduced galling in beet plants infested by M. incognita by up to 86% [47]. However, in the 120 days after transplanting evaluation of our study, it performed poorly and matched the untreated control population.…”
Section: Discussioncontrasting
confidence: 49%